Trabalho e ciência para além do Currículo Lattes: vivências e narrativas de docentes pesquisadoras no contexto de programas de pós-graduação da Universidade Tecnológica Federal do Paraná, campus Curitiba-PR - Ribeiro, Claudiane (2023)
The present study analyzed the experiences and narratives of research professors based on the dialogues between work and science. Such elements, which are established in interdisciplinary fields, are also present in the field of knowledge of Organizational Studies. In this way, we seek to analyze the experiences and narratives of research professors who work in Stricto Sensu Programs at UTFPRCâmpus Curitiba, considering it a unique organization, considering it is the only Technological University in Brazil, which has courses historically appropriated by the masculine. It is important to note that in addition to the singularities of the university space, they follow paths with socially, historically and culturally constituted professional responsibilities, such as the various working hours, both formal and domestic work and care for children and family members. The designation of several activities resulted in timely research dynamics that dialogue with aspects related to working conditions, physical and mental health, which are sometimes naturalized within contemporary society. To achieve the objective, analyzes established from classic and contemporary authors were necessary, such as Londa Schienbinger, Heleieth I.B. Saffioti, Margareth Rago, Helena Hirata, Nadia Kovaleski, Nanci Stancki, among others, in which some bring the social and cultural changes of society since the Industrial Revolution and problematizations about the processes of vulnerability and inequalities surrounding women. Theoretical references supported the study carried out with the teachers/researchers who make up the faculty of Postgraduate Programs at UTFPR – Campus Curitiba. To this end, the study was established based on a qualitative, field approach and with documentary support, as it seeks to analyze narratives and experiences, therefore, with aspects related to subjectivities and overflowing meanings. In this way, field research was carried out, using document analysis and semi-structured interviews as data collection instruments. Data analyzes were guided by Content Analysis, with a priori categories: a) the insertion trajectories in Stricto Sensu; b) experiences in the context of Brazilian postgraduate studies and the relationships between personal life and work. In view of the field research developed and subsequently with data analysis, it was noticed that the trajectories in the field of science were mediated by family members and teachers who were part of their trajectories. Likewise, the reports indicate narratives of resistance and the creation of spaces within the scope of research, especially due to the need for permanent reconciliation between the context of professional and personal demands.